The Association Between Preference and Consumption of Vegetables and Fruits on Health and Non-Health University Students in Yogyakarta, Indonesia - Wahyuni, Sri; Aji, Arif Sabta; Triastanti, Resti Kurnia; Herawati, Herni Dwi (Journal of Global Nutrition, 2024)
Fiber content in vegetables and fruits has benefits in preventing various diseases. Lack of consumption of vegetables and fruit can be influenced by various factors, such as preference factors. The difference of preference among students may impact their consumption status. This study aimed to identify the association of preferences with the consumption of vegetables and fruits among health and non-health students.: This was a cross-sectional study with 272 subjects and the data was taken by systematic random sampling. Data were collected using the online FFQ questionnaire which was conducted during November-December 2020 in Alma Ata University Yogyakarta. Data were analyzed using the Chi-Square test using SPSS v.23. This study showed that there was no difference between vegetable and fruit preferences among students (p>0.05). There were differences in the type of vegetable consumption (p = 0.049), and there was no difference in the type and frequency of fruit and vegetable consumption among health and non-health students (p>0.05). This study concluded that there was no difference in preference, type of fruit consumption, the frequency of vegetables, and fruit consumption among health and non-health students. However, there were differences in the types of vegetable consumption among health and non-health students. These findings suggested that the habit of consuming vegetables and fruits needs to be improved as part of their lifestyle.